Multimedia communications, services and security : 7th International Conference, MCSS 2014, Krakow, Poland, June 11-12, 2014. Proceedings - Czyżewski, Andrzej; Dziech, Andrzej (Communications in Computer and Information Science, 2014)
This volume constitutes the refereed proceedings of the 7th International Conference on Multimedia Communications, Services and Security, MCSS 2014, held in Krakow, Poland, in June 2014. The 21 full papers included in the volume were selected from numerous submissions. The papers cover ongoing research activities in the following topics: audiovisual systems, novel multimedia architectures, multimedia data fusion, acquisition of multimedia content, quality of experience management, watermarking technology and applications, content searching methods, interactive multimedia applications, cybercrime countermeasures, cryptography, biometry, as well as privacy protection solutions.